Redefining Representation: Women in Reality Television - Blackstone, Maya D. (Tufts Archival Research Center, 2017)
My research focuses on the representation of women in reality television. I looked at production standards, editing, and producer involvement to examine how women's representation is altered in reality television. While in theory, the "unscripted" nature of reality television gives women the opportunity to create their own characters, the nature of reality television manipulates many women in order to create dramatic storylines and entice viewers. For my thesis I did extensive research on season twenty of The Bachelor, completing a content analysis looking at how stereotypes are seen throughout the program. Through interviews with past participants and viewers, I also looked anecdotally on the impact of reality programs on participants and viewers.